2016
DOI: 10.1080/13670050.2015.1125848
|View full text |Cite
|
Sign up to set email alerts
|

‘I have discovered new teaching pathways’: the link between language shift and teaching practice

Abstract: The aim of this paper is to explore how a shift1 in the language of teaching and learning can lead university lecturers of a range of disciplines to reflect on and innovate their teaching approaches. The paper is based on a case study of a single university in the north of Italy which is gradually becoming a bilingual higher education institute. Through a thematic analysis of questionnaire and interview data gathered from 53 lecturers who attended professional development courses designed to support them in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
6
33
0
Order By: Relevance
“…For example, Italian university lecturers expressed a belief that their English was inadequate, and that students would find it difficult to understand them, leading to possible incorrect language learning on the part of the students (Pulcini & Campagna 2015;Campagna 2016). Also in Italy, at least ten out of 53 participants in Guarda & Helm's (2016) study considered their own language skills as one of the major sources of difficulty in teaching on EMI programmes. Less concern was expressed by Italian Engineering lecturers who all reported feeling quite confident with their English and did not consider they faced problems interacting with students, or evaluating students' progress (Francomacaro 2011).…”
Section: Teacher and Student Beliefs About Emimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Italian university lecturers expressed a belief that their English was inadequate, and that students would find it difficult to understand them, leading to possible incorrect language learning on the part of the students (Pulcini & Campagna 2015;Campagna 2016). Also in Italy, at least ten out of 53 participants in Guarda & Helm's (2016) study considered their own language skills as one of the major sources of difficulty in teaching on EMI programmes. Less concern was expressed by Italian Engineering lecturers who all reported feeling quite confident with their English and did not consider they faced problems interacting with students, or evaluating students' progress (Francomacaro 2011).…”
Section: Teacher and Student Beliefs About Emimentioning
confidence: 99%
“…The authors report that the main motivation for taking part was the lecturers' desire to up-skill in English language rather than consider changing methodology. In Italy, Guarda & Helm (2016) report on a seemingly successful development programme which involved over 50 lecturers in presenting lectures, and seminars followed by group discussions. Pre-and post-analysis of views expressed by participants shows some promising change of perceptions and greater willingness to interact with students in English, as well as to consider student needs.…”
Section: Professional Development Of Emi Teachersmentioning
confidence: 99%
“…They demonstrated that Italy has been "slow to internationalise" (p. 5) despite an Italian law of 2010 calling for greater mobility of faculty and students, more co-operation among universities, and an increase in programmes taught through a second language. According to online data from Universitaly reported in Guarda and Helm (2016), there are 55 universities offering 245 "English Taught Programmes" (ETPs, another term for EMI), 226 of which are at Master's level and 19 at Bachelor's level. This represents a 72% rise in just one year.…”
Section: Emi In Italy Austria and Poland: A Brief Overviewmentioning
confidence: 99%
“…Since the first introduction of EMI in the early 2000s, which was then reinforced by legislation in 2010, Italian HEIs have moved fast, and competitively, in introducing EMI at graduate, and more recently undergraduate levels. In 2016, 55 universities offered 245 ETPs, of which 19 were at undergraduate level (Guarda, Helm 2016). This is an extraordinary increase of over 70% on the previous year.…”
mentioning
confidence: 93%
“…Students with high self-evaluation were the most critical of classroom atmosphere, and what they felt was a lack of debate and discussion. It becomes clear that further, more empirical investigation is necessary to evaluate further this correlation, and whether it is a result of language issues, or teaching strategies as discussed by Guarda and Helm (2016).Terminology is an essential element of the EMI classroom and often the source of difficulty for students. Participants in this study were extremely satisfied that they had been able to learn the necessary terminology, and did not see language as creating difficulties, although it was the IN students who were less confident.…”
mentioning
confidence: 99%